Minimally invasive Approach in Surgical Treatment of Papillary Thyroid Cancer - Heneritt , Emilia F. (Academic Journal of Clinicians, 2024)
Background: Papillary thyroid cancer is the most common type of thyroid malignancy, requiring surgical intervention for definitive treatment. This original article explores the utilization and outcomes of a minimally invasive approach in the surgical treatment of papillary thyroid cancer, focusing on its advantages, safety, and long-term outcomes. Methods: A retrospective analysis was conducted on patients diagnosed with papillary thyroid cancer who underwent minimally invasive surgical procedures. The minimally invasive approach included techniques such as endoscopic or robotic-assisted thyroidectomy, aiming to reduce surgical trauma, improve cosmetic outcomes, and minimize postoperative complications. Surgical outcomes, including operative time, blood loss, length of hospital stay, complication rates, and oncological outcomes, were evaluated. Results: The original article presents the findings on the utilization and outcomes of a minimally invasive approach in the surgical treatment of papillary thyroid cancer. The minimally invasive techniques demonstrated favorable outcomes, with shorter operative times, reduced blood loss, and decreased hospital stays compared to traditional open procedures. The complication rates were comparable, and oncological outcomes, including disease recurrence rates and survival rates, were not compromised by the minimally invasive approach. Additionally, the minimally invasive approach offered improved cosmetic results, leading to enhanced patient satisfaction. Conclusions: The utilization of a minimally invasive approach in the surgical treatment of papillary thyroid cancer offers several advantages without compromising oncological outcomes. This approach reduces surgical trauma, resulting in shorter operative times, reduced blood loss, and shorter hospital stays. The comparable complication rates and favorable cosmetic outcomes make it an attractive option for patients. Further studies are needed to validate these findings and establish guidelines for the optimal application of the minimally invasive approach in the management of papillary thyroid cancer.